Fabrication and Dissolution Studies of Self-micro–Emulsifying Drug Delivery System (International Journal of Food and Nutritional Sciences, 2022)
The majority of active pharmaceuticals, which are in the parlance, do suffer from hindrances of poor aqueous solubility. The scientific fraternity across the globe has explored numerous approaches to address the low bioavailability of the drugs. One amongst such strategies is delivering the actives via lipid-based carrier systems. The present investigation was undertaken to enhance the solubility of simvastatin (a cholesterol-lowering medicine), employing several oils and a blend of surfactants and co-surfactants. The ratios were optimized based on a phase diagram. There was a formulation of 11 batches of SMEDDS formulations having different compositions. The preparations were subjected to dissolution studies. The maximum solubility of the drug was determined as 143 ± 5.3 mg in Lauroglycol 90. The average drug release was in the range of 88 ± 1.6-101 ± 2.5 %. The addition of a stabilizer (Transcutol) does not significantly affect the drug release. It could be suggested at this juncture that simvastatin may be more bioavailable in case confined within a lipid-based delivery system.